Seasonal Changes in Activity, Sex Composition and Areal of the Tick Ixodes ricinus (Acari, Ixodida) in the Landscape-Geographical Regions of Ukraine - Akimov, I.A.; Nebogatkin, I.V. (Вестник зоологии, 2010)
Data on seasonal activity of adults, nymphs and larvae of the sheep tick Ixodes ricinus Linnaeus are presented based on examination of our own collections for the period from 1977 to 2001 and archival materials for the period from 1953 to 2000, as well as data on changes in its natural habitat that now covers the whole territory of Ukraine. The period of activity in I. ricinus imagoes becomes longer from north to south and from west to east. In Ukrainian populations of I. ricinus, females slightly dominate (on average 52.44 ± 0.55%). The seasonal differences in the sex ratio are as follows: males are more abundant in springtime, females — in autumn. Significantly larger numbers of females (on average 52–60%) are registered on population peaks, and larger numbers of males — on their decrease. На основе анализа собственных сборов (1977–2001 гг.) и архивных материалов (1953–2000 гг.) приведены о сезонных изменениях активности взрослых, нимф и личинок европейского лесного клеща, а также изменение ареала вида, который распространяется на всю территорию Украины. Продолжительность активности половозрелых фаз I. ricinus увеличивается с севера на юг и с запада на восток. В популяциях европейского лесного клеща в Украине незначительно преобладают самки (в среднем 52,44 ± 0,55%). Обнаружены сезонные различия в соотношении полов: самцов больше в весеннее время, а самок — в осеннее. Достоверно большее количество самок (в среднем 52–60%) зарегистрировано на пиках численности, а самцов — на спадах.